Влијанието на фискалната политика врз развојот на малите и средните претпријатија – случајот на Република Македонија - Алими, Гарип (Економски факултет, УКИМ, Скопје, 2017)
So as to understand the significance of the elaboration of this topic, the attention was primarily given to the rule of the small economy in the modern economies - developed and underdeveloped, based on the participation of the small and medium enterprises (SMEs), their contribution in generating the Gross Domestic Product (GDP), in solving the problems related to the unemployment and in promoting the overall social-economic development. Further, as it is indicated below, the influence of the fiscal policy is analyzed. Thereat, the effects of the taxes and other fiscal contributions are primarily analyzed, followed by a special attention given to the fiscal incentives that are of general use by all the economic subjects, irrespective of their size. Then, the measures that are provided as specific ones for the SMEs are especially treated. Because the work is dealing with the influence of the fiscal policy, the effects of the budget expenditures in instigating the start and the development of small businesses are also analyzed. The theoretic observations of the possible measures and effects of the fiscal policy on the development of SMEs are broadened by the analysis of the influence of the fiscal and tax policies whose aim is to improve the small economy as well as the activities of the SMEs in the European Union (EU) as a political-economic community. The rich systemic set of instruments and the specific fiscal measures for the functioning of the SMEs in the United States of America (USA) is also analyzed. The analysis of the situation in the EU and in the USA concerning the share, the status and the stimulation of the development of the small economy enables a critical and in the same time inspirational approach to the analysis of the fiscal system. Besides the fiscal policy, the systemic solutions, the legal framework, the possibilities of extending the loans and providing the financial resources from nonbanking sources that are also important to the small economy are also analyzed. However, the main focus in the dissertation is given to the empirical analysis of the economic and financial situation of the SMEs (enterprises) in the Republic of Macedonia. The influence of the fiscal policy on the socio-economic development and the economic circumstances in the Tetovo region is analyzed, supplemented by the analysis of the influence of the tax policy on the development of small and medium businesses in this region. The analysis is based on the evaluation of legal solutions as well as to the implemented fiscal system reforms and the changes in the tax policy that were verified in the years since the Republic of Macedonia gained the independence. In the analysis the scope of the fiscal obligations and paid taxes, contributions and other payments so as to evaluate the influence of the fiscal factor on the development of small and medium businesses in the Tetovo region - historically and in the current times are also taken into account.
Докторска дисертација одбранета во 2017 година на Економскиот факултет во Скопје, под менторство на проф. д–р Живко Атанасовски.
Keywords: fiscal policy, budget expenditures, effects on taxes, empirical analysis